Influencing Factors of Shale Permeability in the Longmaxi Formation, Southern Sichuan Basin and Northern Yunnan-Guizhou Depression - Changcheng Han; Geng Liu; Cunfei Ma; Ming Qi; Yi Yang; Guan Li (Geofluids)
The current paper studies the influencing factors of permeability in shales of the Longmaxi Formation, located in the southern Sichuan Basin, China. The methodologies used in the present study include overburden pore permeability experiments, whole rock analysis and geochemical tests, NMR measurements of fluid saturation, pore size distribution and specific surface area distribution, SEM and extraction of pore structure parameters, and core analysis. The results show the following: (1) high TOC and high maturity generate a large number of organic pores, which may improve the permeability of shale. (2) Mineral composition and rock relative permeability also have influence on permeability to a certain degree, since different minerals have different effects on shale permeability. Clay in the study area has an adverse effect on permeability. The results show that the organic-rich siliceous clay mixed shale facies in this area has the best permeability. (3) A large specific surface area and total pore volume are associated with good shale permeability, while average pore size does not correlate with permeability. A small fractal dimension of pore morphology and simple pore structure result in good permeability, and bedding is the key controlling factor for the anisotropy of shale permeability. (4) Water in shales can influence the permeability of microfractures by binding to clay minerals. Low permeability in shales with high bound water saturation suggests that water and clay mineral absorption may block flow channels, resulting in poor permeability. The purpose of this study is to clarify the influencing factors on shale permeability of the Longmaxi Formation in the study area and to provide a reference for the exploration and development of shale gas in this area of the Sichuan Basin.